Prevalence of post-traumatic stress disorder and physical health complaints among Portuguese Army Special Operations Forces deployed in Afghanistan. - Osório, Carlos (2012)
BACKGROUND: Investigations conducted with several U.S. and U.K. military veterans returning from Afghanistan and Iraq have reported the existence of mental and physical health complaints. METHODS: A total of 113 participants completed a self-report questionnaire that assessed post-traumatic stress disorder (PTSD) symptoms, physical health complaints, and reported illnesses. RESULTS: Overall, 2.7% of the participants reported symptoms compatible with a PTSD diagnosis and 8.8% have partial PTSD. The most common physical health complaints were back pain, fatigue, and muscle pain. In addition, participants experienced gastrointestinal, nervous, and respiratory diseases. PTSD symptoms further explain the variance in physical health complaints after controlling for the contribution of reported illnesses to the same variables. CONCLUSIONS: The prevalence of PTSD in the study sample is low, but PTSD symptoms are significantly related to physical health complaints and reported illnesses and explain the variance in physical symptoms. This fact should be considered by clinical support services, and military personnel with physical complaints should be screened for PTSD. These Portuguese results obtained from participants belonging to a well-prepared Special Operations Forces group contribute to a better understanding of the physical and mental impact of the war in Afghanistan.